2011
DOI: 10.2337/dc10-1985
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy Is Related to Both Endothelium-Dependent and -Independent Responses of Skin Microvascular Flow

Abstract: OBJECTIVEEndothelial dysfunction has been hypothesized as a possible pathogenic factor in the development of diabetic retinopathy (DR). We examined the relationship of DR to endothelium-dependent and endothelium-independent responses in skin microvascular flow.RESEARCH DESIGN AND METHODSParticipants consisted of 224 individuals with diabetes: 85 with type 1 diabetes and 139 with type 2 diabetes. Sodium nitroprusside (SNP) and acetylcholine (ACh) were delivered across the skin by iontophoresis. Laser Doppler fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 21 publications
(27 reference statements)
2
41
1
Order By: Relevance
“…We recruited 224 patients (18-70 years of age) with diabetes (85 with type 1 and 139 with type 2), as previously described [4][5][6][7]. We excluded participants who had a history of epilepsy or glaucoma, had undergone previous vitreal surgery, and/or had a cataract on examination.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…We recruited 224 patients (18-70 years of age) with diabetes (85 with type 1 and 139 with type 2), as previously described [4][5][6][7]. We excluded participants who had a history of epilepsy or glaucoma, had undergone previous vitreal surgery, and/or had a cataract on examination.…”
Section: Study Populationmentioning
confidence: 99%
“…Iontophoresis delivers vasodilators (SNP and ACh) across the skin using a weak electrical current, with blood flow measured by laser Doppler flowmeter (Moor Instruments, Axminster, UK) [5].…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] The abundant vascular network in skin provides an accessible and common vascular bed for assessing vascular hemodynamic response. 6,7 In recent years, the skin vascular function started to draw widespread attention as a potential research biomarker to predict cardiovascular diseases 8 and diabetic retinopathy 9 or as a prognostic marker for evaluating drugs effect on the microcirculation. 10 Previous studies showed diabetes could cause various skin vascular changes, including microvascular structure, 11 vascular density and diameter, 12 blood flow and blood oxygen, 13,14 and vascular permeability.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Moreover, some clinical studies have reported that vasodilation of the retinal vessels elicited by flicker stimuli deteriorates in patients with these diseases. [13][14][15] However, the involvement of glial cells in regulating the RBF in response to flicker stimulation has not been well determined. 16 Although some reports have focused on the role of glial cells in metabolic autoregulation in neurovascular coupling, 2,6,[16][17][18] the role in the retinal vasculature remains unclear.…”
mentioning
confidence: 99%